The adsorption of nitrogen and argon by evaporated films of sodium chloride - Rodgers, Allen L (Department of Chemistry, 2016)
An ultra-high vacuum apparatus has been designed and constructed. Pressures of the order of 1 x 10⁻⁸ torr have been attained routinely. The adsorption of nitrogen by Pyrex has been investigated and the results obtained have shown good agreement with those in the literature. Rigorously cleaned evaporated films of sodium chloride have been prepared and the adsorption of nitrogen and argon by them has been investigated. Isosteric heats and entropies of adsorption have been determined and theoretical entropies calculated. The appearance of a group of sites of uniform activity, hitherto unavailable owing to contamination of the surface, is postulated. The adsorption of nitrogen and argon has been found to be reasonably well represented by the immobile, localized model with indications of the adsorbed argon molecules occupying a different set of sites from the adsorbed nitrogen. Two novel methods for the preparation of evaporated films of alkali halides are suggested.